ALIH FUNGSI LAHAN: POTENSI PEMICU TRANSFORMASI DESA - KOTA (Studi Kasus Pembangunan Terminal Tipe A âKertawangunanâ) - Nurjanah, Evi Novia; Purwandari, Heru (Jurnal Sosial Ekonomi Pertanian, 2012)
Land conversion is not only about agrarian transformation but also its effect on social transformation within area that has changed. Kertawangunan terminal is built to facilitate Kuningan regency in reaching the development goal as a center of agriculture so that the terminal is emerged to facilitate agriculture commodity. Unfortunately, tiny converson has a big impact on sustainability of agriculture in terms of triger padi field transformation in surrounding. Implication of farm conversion to area development of Kuningan Regency gets bearing with changing plan sets region room, economic growth priority, and gross regional domestic product dominant. In this context, development that expected to improve marketing process becomes obstacle for expanding agriculture product itself. Key Words: Land Conversion, Agrarian Transformation, Social Transformation